Pelatihan Pijat Bayi Untuk Kondisi Sembelit Di Posyandu Balita Abadi Sejahtera - Shella Dhika Rahmawati; Ni Kadek Krisna Dwi Patrisia; Almita Ratu Rifanda; Sofia Mardiana; Friesca Persityara Agatha; Aulia Ayu Kusuma (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Constipation is a digestive problem that can be experienced by anyone, both parents and children. When it occurs in children, constipation which causes pain in the stomach will certainly interfere with their daily activities. There are various causes of constipation in children, ranging from cow's milk allergies, dehydration, to poor diet. Based on the data obtained, there were 2 toddlers with stomach complaints of constipation. Some parents underestimate constipation in toddlers and don't know how to reduce constipation. Based on these data, it is necessary to carry out community service "Baby Massage Training for Constipation Conditions at Posyandu Abadi Sejahtera" as a solution to increase the knowledge and skills of cadre administrators and parents. This activity consists of field visits, face-to-face training, home visits and ongoing monitoring. on line. The output target is achieving community empowerment and increasing skills, publishing the results of community service in national journals and electronic media. The results of this activity showed an increase in knowledge and skills in caring for toddlers who experience constipation.